(3GdeSJWGH aj JGQjN YdeGA GdRjOjI GdCWjGHs - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO,J (B1099 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA hQKI GdCfHjG AhGdeQSdjf hHYO aEfg deG cGf Yde GdJGQjN ahGFO LdjdI hcGf YdeGA GdaQb bO EYJfhG HJGQjN YdeGFge hde CQ dCUMGHfG ef GdSGOI hGdTjYI SHHkG ef GdJhGQjN s
(3BNQgG (B:s
(3hbO QCjfG Cf fNJe GdcJGH ai gPG GdehVY , aEf GdJGHYjf ef GdYdeGA dGjRGdhf hCMhGdge eYQaI de jba Ydi TF ef GdJhGQjN dChdFc ef GdMGLI GdVQhQjI hcGf JCdja gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3GfJgi ef JCdjag SfI (B1075(3g`s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI Ydi WQJgG JedcGJ MOjKI cJHJ GdahGJM HGdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs